The Difference in Cranium Morphological Characteristics of Homo sapiens, Pithecanthropus erectus, and Pithecanthropus soloensis - Rudin, Nur Ahmad; Jati, Gagas Kuncoro (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Modern human (Homo sapiens) are living things that have evolved through the evolutionary process from a kind of Primates. The history of human evolution is studied through discovery of fossilized body parts in layers of the earth. Early human Pithecanthropus is the most type commonly found in Indonesia, such as Pithecanthropus erectus and Pithecanthropus soloensis. Early human have different physical characters from modern human. Morphological characters are commonly used for identification of early human fossils. Cranium plays an important role in fossil identification because it has different variations between species as a result of evolution. This study aims to determine the differences in cranium morphological characters from H. sapiens, P. erectus, and P. soloensis. The research was conducted by observing the morphological characters of cranium. Data analysis with descriptive qualitative. The difference in cranium morphological characteristics of H. sapiens, P. erectus, and P. soloensis are the shape of cranium in verticalis norm, parietal tuber, and supraorbital torus. Cranium morphological characters is simply and reliable to identify the types of hominid species.